Examination of the Optical and Thermal Characteristics of Solid Materials - Ali Soluman Ali Hassien (African Journal of Advanced Pure and Applied Sciences, 2024)
For a variety of technological applications, the research of solid materials’ thermal and optical properties is essential. A material’s reaction to heat is determined by its thermal properties, which include thermal conductivity, specific heat capacity, thermal expansion, and thermal diffusivity. Its interaction with light is controlled by optical characteristics, including transmittance, absorbance, reflectance, refractive index, and optical bandgap. To precisely assess these attributes, experimental procedures like as ellipsometry, spectroscopy, and thermal analysis are used. Electronics, energy storage, and optoelectronics can all benefit from the design of materials with enhanced heat transfer, energy efficiency, and optical capabilities made possible by an understanding of the ability to manipulate these qualities. We hope that this paper will be useful and a reference for researchers in the field.